2012
DOI: 10.4236/ojvm.2012.21003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects and Clinicopathological Findings in Cats Naturally Infected with Feline Leukemia Virus (FeLV) and/or Feline Immunodeficiency Virus (FIV)

Abstract: Infections produced by feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV), two of the most prevalent pathogens in cats, range from passing unnoticed to presenting a wide variety of clinical signs. Different epidemiological, clinical, hematological and virological parameters were analyzed in 78 FIV-and/or FeLV-infected cats. FeLV-infected (FeLV + ) cats were considerably younger than FIV-infected (FIV + ) cats, and in general were seen to have a more severe disease than FIV + cats. Around one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 16 publications
5
35
0
5
Order By: Relevance
“…Doubly infected cats showed less severe symptoms than mono-infected animals, and the results were in general closer to those of FIV+ than FeLV+ cats (COLLaDO et al, 2012), which was also observed in our study.…”
Section: N Rudan Et Al: Clinical and Haematological Parameters Of Fsupporting
confidence: 77%
See 3 more Smart Citations
“…Doubly infected cats showed less severe symptoms than mono-infected animals, and the results were in general closer to those of FIV+ than FeLV+ cats (COLLaDO et al, 2012), which was also observed in our study.…”
Section: N Rudan Et Al: Clinical and Haematological Parameters Of Fsupporting
confidence: 77%
“…Hematological (COLLaDO et al, 2012). In our research as well FIV + cats were generally younger than FeLV + cats.…”
Section: N Rudan Et Al: Clinical and Haematological Parameters Of Fmentioning
confidence: 80%
See 2 more Smart Citations
“…Blood samples were collected from these animals in their homes. The inclusion criteria were: 1) it needed to be asymptomatic, i.e., clinical examination did not show any abnormalities suggestive of systemic disease such as vomiting, diarrhea, weight loss, nasal secretion, or neoplasia (Collado et al, 2012), 2) it had to be 6 months of age or over. In addition to these animals, 30 samples from stray cats were sent by veterinarians at the zoonosis control centers of these cities.…”
Section: Location Of the Study And Sampling Designmentioning
confidence: 99%